Neurolaw: trends and perspectives in crime investigation - Arenova, L.K. (Bulletin of the Karaganda University “Law Series”, 2022)
The article discusses new achievements of neuroscience in legal relations in general and in particular in the practice of investigating certain types of crimes, the possibility of using such scientific knowledge as an interdisciplinary field. In modern society, there is an active surge of research in psychology, medicine, biology, physiology, physics, and other sciences of the natural and exact cycle, which has formed a direction defined as neuroscience. Neuroscience provides scientific ideas about the brain and about the functioning of the brain, the mechanisms of mental activity, reaction of the brain to phenomena, events, and actions. The indications allow us to assert that the implementation of a public interdisciplinary approach is carried out both in the actual research and practical activities, the particular relevance of which is observed precisely in the field of rights and legal relations. The leading approach to the study of issues related to the trends and prospects of neurolaw is the system-activity approach and the method of analyzing state legislation in this area. As a result, the article presents reasonable provisions that allow to use the interaction of two spheres – neuroscience and law – and offers a more accurate, comprehensive approach to legal analysis and the establishment of legal norms and standards. Consideration of neuroscience research as a new scientific approach, and their integration into the field of law and legal relations, allows us to solve a number of basic legal problems, which include formation in modern Kazakhstani legal science of such a scientific and practical direction as neurolaw, which is in line with modern international scientific interests; the possibility of using such an interdisciplinary area as neurolaw in lawmaking, as well as in the practice of effective investigation of certain types and groups of crimes and judicial activities, to achieve judicial truth; ethical aspects of legitimate extraction of information from the brain of the examined person.